A systematic review of the health and well-being impacts of school gardening: synthesis of quantitative and qualitative evidence - Ohly, Heather (BMC Public Health, 2016)
BACKGROUND: School gardening programmes are increasingly popular, with suggested benefits including healthier eating and increased physical activity. Our objectives were to understand the health and well-being impacts of school gardens and the factors that help or hinder their success. METHODS: We conducted a systematic review of quantitative and qualitative evidence (PROSPERO CRD42014007181). We searched multiple databases and used a range of supplementary approaches. Studies about school gardens were included if they reported on physical or mental health or well-being. Quantitative studies had to include a comparison group. Studies were quality appraised using appropriate tools. Findings were narratively synthesised and the qualitative evidence used to produce a conceptual framework to illustrate how benefits might be accrued. RESULTS: Evidence from 40 articles (21 quantitative studies; 16 qualitative studies; 3 mixed methods studies) was included. Generally the quantitative research was poor. Evidence for changes in fruit and vegetable intake was limited and based on self-report. The qualitative research was better quality and ascribed a range of health and well-being impacts to school gardens, with some idealistic expectations for their impact in the long term. Groups of pupils who do not excel in classroom activities were thought to particularly benefit. Lack of funding and over reliance on volunteers were thought to threaten success, while involvement with local communities and integration of gardening activities into the school curriculum were thought to support success. CONCLUSION: More robust quantitative research is needed to convincingly support the qualitative evidence suggesting wide ranging benefits from school gardens.